A Simple and Efficient Strategy for Preparing a Cell‐Spheroid‐Based Bioink. Issue 15 (17th June 2022) - Sun, Weiyan; Zhang, Jiahui; Qin, Yechi; Tang, Hai; Chen, Yi; Lin, Weikang; She, Yunlang; Zhang, Kunxi; Yin, Jingbo; Chen, Chang
Abstract: Cell spheroids are a promising bioprinting building block that can mimic several physiological conditions in embryonic development. However, it remains challenging to efficiently prepare cell‐spheroid‐based bioink (Sph‐bioink) with favorable printability and spheroid fusion ability. In this work, a poly( N ‐isopropylacrylamide) (PNIPAAm)‐based porous hydrogel is developed as an "all‐in‐one" platform for Sph‐bioink preparation. On the one hand, the nonadhesive porous structure in hydrogels is an effective tool for fabricating adipose‐derived stem cell (ASC) spheroids in high yield, and the hydrogel itself also serves as a "carrier" for conveniently transferring cell spheroids to the bioprinter. On the other hand, the integration of redox/thermo‐responsiveness allows the hydrogel to shift from a solid spheroid‐making tool to an extrudable bioprinting medium that is sensitive to temperature. These features enabled a simple procedure for preparing Sph‐bioink, in which the cell spheroids were densely packed to retain fusion capability. The present study also demonstrates that ASC spheroids formed in hydrogels have good biological preservation and superior chondrogenic differentiation, and verified the feasibility of using Sph‐bioink to build custom‐shaped mature cartilage. In conclusion, this strategy provides a simple, efficient, and standardized approach for Sph‐bioink preparation, making it possible to produce tissue‐engineered constructs with accelerated maturation and functionalization. Abstract : A PNIPAAm‐based porous hydrogel is designed as an "all‐in‐one" platform that combines multiple steps for efficiently preparing cell‐spheroid‐based bioink (Sph‐bioink), in which the cell spheroids are densely packed to retain fusion capability. Adipose‐derived stem cell spheroids in Sph‐bioink exhibit good biological preservation and superior chondrogenic differentiation, and can be assembled to build a custom‐shaped mature cartilage through bioprinting.